Therapeutic itinerary of stroke survivors in a Nigerian tertiary hospital - Chidozie Emmanuel Mbada; Oluwayemisi Mary Ogunleye; Abiola Oladele Ogundele; Olufemi Oyeleye Oyewole; Adekola Babatunde Ademoyegun; Adebimpe Olayinka Obembe; Francis Fatoye (Universidade Federal do Ceará, 2021)
Objective: to analyze the therapeutic itinerary of stroke survivors from stroke occurrence to rehabilitation. Methods: therapeutic itinerary - route taken by individuals to solve their health problems, of 12 stroke survivors was explored using in-depth interviews and was thematically analyzed. Results: stroke survivors' routes were influenced by type of stroke and the state of the patient at onset of stroke. Lack of capacity facilitates vacillation from private to the public hospital settings. Entry into physiotherapy was dependent on self-referrals and referrals from physicians who often serve as gatekeeper of patients. Stroke significantly affected social life of stroke survivors, and the extent of stroke impairment and unmet expectations promotes medical pluralism among the survivors. Conclusion: stroke survivors are involved in intricate and lengthy therapeutic itineraries that are characterized by multiple care seeking practice.